1992
DOI: 10.1111/j.0022-3646.1992.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

FATTY ACID CONTENT AND CHEMICAL COMPOSITION OF FRESHWATER MICROALGAE1

Abstract: Fatty acid (FA), total lipid, protein, amino acid, carbon, nitrogen, and phosphorus content was analyzed in 24 samples of freshwater microalgae. The samples originated from batch, continuous, or mass cultures in various growth phases and from net samples from lakewater. FA were analyzed quantitatively by using an internal standard in a GLC system and expressed as mg·g−1 dry weight (DW). The FA of one group of blue‐greens (e.g. Oscillatoria and Microcystis) were similar to those of the greens with higher amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
336
4
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(371 citation statements)
references
References 65 publications
21
336
4
3
Order By: Relevance
“…Volcani, 1966;Kattner, 1993 , marine Ž Dinophyceae Mayzand et al, 1976;Fraser et al, . 1989;Ahlgren et al, 1992 , as well as Haptophyceae Ž . Sargent et al, 1985, Conte et al, 1994 .…”
Section: Biomarkers As Organic-carbon Source and Environmental Indicamentioning
confidence: 99%
See 2 more Smart Citations
“…Volcani, 1966;Kattner, 1993 , marine Ž Dinophyceae Mayzand et al, 1976;Fraser et al, . 1989;Ahlgren et al, 1992 , as well as Haptophyceae Ž . Sargent et al, 1985, Conte et al, 1994 .…”
Section: Biomarkers As Organic-carbon Source and Environmental Indicamentioning
confidence: 99%
“…Sargent et al, 1985, Conte et al, 1994 . Shortchain fatty acids, however, are also found in lacus-Ž trinerfreshwater environments Ahlgren et al, 1992; . Leveille et al, 1997 .…”
Section: Biomarkers As Organic-carbon Source and Environmental Indicamentioning
confidence: 99%
See 1 more Smart Citation
“…and had a measured ratio to chl a of 0.3 (Table 5). It was assumed that the contribution of 18:4 by chlorophytes (which are known to produce C 18 65 PUFAs) was negligible, since previous studies have shown that chlorophytes only produce small amounts of 18:4 compared to total lipids (~3%) (Volkman et al 1989, Ahlgren et al 1992). These 2 approaches were generally in broad agreement ( Table 6), suggesting that Oscillatoria spp.…”
mentioning
confidence: 99%
“…Традиционно основными факторами, ограничивающими рост первичных консу-ментов при высокой биомассе продуцентов, считаются стехиометрическое соотношение C:N:P (Giani, 1991;Stelzer and Lamberti, 2002;Acharya et al, 2004;Cross et al, 2005;Ventura et al, 2008), содержание незаменимых по-линенасыщенных жирных кислот (ПНЖК) семейства ω3 (Brett and Muller-Navarra, 1997;Boersma et al, 2001) Отсутствие интереса к изучению амино-кислот (АК) при исследовании качества пищи гидробионтов вызвано устойчивым представ-лением о постоянстве состава АК микроводо-рослей в отличие от состава ПНЖК (Ahlgren et al, 1992;Brown et al, 1997;Muller-Navarra, 2008). Этим объясняется столь незначитель-ное количество накопленных к настоящему # 87 # Anzhelika A. Kolmakova, Michail I. Gladyshev… Estimation of Amino Acid Quality of Food for Benthic Invertebrates… времени данных об аминокислотном составе микроводорослей.…”
Section: Introductionunclassified